Planning for a Farm Tour: Keeping the Conversation Fresh - Claire Mitchell; Joy N. Rumble (EDIS, 2015)
Hosting tours at your farm can be a great way to market your products and your farm’s brand. Tours let you tell potential customers how you grow your food, why they should buy it, and who you are as a farmer. This 3-page fact sheet discusses these topics and provides logistical advice for planning and executing a successful farm tour. Written by Claire Mitchell and Joy N. Rumble, and published by the UF Department of Agricultural Education and Communication, August 2015.